Decorated Ising nanoparticles with high critical temperature. (1st February 2020) - Kaneyoshi, T.
ABSTRACT: The phase transitions of two magnetic nanoparticles and their decorated nanoparticles are examined by the effective-field theory with correlations. They are consisted of two isolated paramagnetic Ising nanoparticles coupled by an exchange interaction. It is discussed whether a ferromagnetic nanoparticle with a transition temperature TC ( N ) larger than that ( TC ( B )) of a bulk ferromagnetic material is possible.